Fuzzy analytic hierarchy based approach for supplier selection - (:unkn) unknown (My University, 2003)
For solving the problem of complex multi-criteria decision-making for supplier selection the fuzzy analytic hierarchy process (FAHP) approach is proposed. By a case study in TV production suppliers the FAHP approach was implemented. Based on the results the TV suppliers were evaluated and the best one selected. FAHP approach was compared with conventional approach. It provided better evaluation of TV suppliers in comparison with the traditional approach. FAHP approach could be applied in other areas for production supplier selection. © 2003 by The Haworth Press, Inc. All rights reserved.
Keywords: Fuzzy analytic hierarchy process(FAHP); Multi-criteria technique; Supplier selection